Akomodasi Pesantren Terhadap Kebijakan Pendidikan Nasional - Muhammad Alqadri Burga; Azhar Arsyad; Muljono Damopolii; Andi Marjuni (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2019)
This research aims to analyze the dynamics of Pondok Pesantren DDI Mangkoso in accommodating national education policies. The method of this research is qualitative with a phenomenological approach whose data is collected through observation, interviews, and documentation. The results of the research indicate that the status of Pondok Pesantren DDI Mangkoso as a traditional Islamic education institution still existed despite carrying out modern developments by maintaining five roles, namely: the place of transmission of classical Islamic sciences, daâ€™wah institutions, preserving Islamic traditions, the center of reproduction of scholars, and place of community service and development. Changes in the position of pesantren in national education policy during the period 1989-2018 have implications for the education policy of Pondok Pesantren DDI Mangkoso whose dynamics are divided into three stages, namely: institutional transformation, integration of curriculum, and application of a culture-basedÂ  inclusive paradigm. The form of accommodation for the national education policy by Pondok Pesantren DDI Mangkoso is the opening of formal education institutions at all levels of education. Various obstacles in the accommodation are the struggle of organizational culture and structure, limited resources, and lack of community participation.